Review : physico-chemical modification as a versatile strategy for the biocompatibility enhancement of biomaterials - John, Agnes Aruna Runa (Royal Society of Chemistry, 2015)
A biomaterial can be defined as a material intended to interface with biological systems to evaluate, treat, augment or replace any tissue, organ or function of the body. Major problems associated with biomaterials are their properties and biocompatibility, which need to be tackled and resolved before promoting a particular biomaterial to the market or implanting it into a biological system. To enhance the biocompatibility of the biomaterials, several surface modification strategies, such as physico-chemical, mechanical and biological modifications, have been explored. In this review, some recent applications of physico-chemical modification technologies, such as alteration in the structure of a molecule by chemical modification, surface grafting, abrasive blasting and acid etching, surface coatings, heat and steam treatment for medical materials such as polymers, metals, ceramics and nanocomposites are discussed. This article will promote physico-chemical modification as a versatile technology in surface engineering to improve the properties and biocompatibility of medical materials. Furthermore, it will instigate the growth of the biomaterial market with various high quality biomaterials.